The Use of Turmeric (Extracts and Squeeze) to Detect Plaque on Teeth - Nike Haryani; Erma Mahmiyah; M. Ibraar Ayatullah (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2019)
Turmeric is one of the original spices and medicinal plants from the Asian region. The benefits of the turmeric plant are good as a complement to cooking spices, herbs/medicines, or to maintain health and beauty. Turmeric can also be used as a coloring agent, such as food coloring agents and dyes for woven fabric crafts. Turmeric plants are easy to find, so turmeric can be used as a substitute for disclosing solution (plaque detection liquid). This turmeric plant is very easy to obtain and does not incur high costs in its management. This study aimed to determine the effectiveness of using turmeric (extract and juice) to detect plaque in teeth in 2019. This type of research uses a quasi-experimental type. The population in this study, namely level 1 military service, amounted to 76 people. The sample used is by using a purposive sampling technique totaling 20 respondents. The results showed an average difference between disclosing solution, 100% turmeric extract, 75% turmeric extract, and 100% turmeric juice. The average disclosing solution was 36.34, 100% turmeric extract 64.50, 75% turmeric extract 79.95, and 100% turmeric juice 90.00. The results of the one-way ANOVA test were sig 0.000 <0.05, meaning that there was an average difference between these variants, from the research results of turmeric extract and turmeric juice could detect plaque but were less effective as a substitute for disclosing solution in plaque detection.